The Effects of Using MS Powerpoint as E-Learning Material to the Academic Performance of the Senior High School Students - Emralino, Joanna B.; Nartea, Mecmack (International Journal of Psychosocial Rehabilitation, 2020)
MS Powerpoint is the most commonly used program in the academe in terms of lesson delivery inside the classroom. Based from different surveys who used MS Powerpoint as their tool in deploying their lessons. It is noted that with the use of the software, students were able to better understand the lessons compared to the traditional ways of delivering the lessons. This assumption enthused the researchers to conduct a study to prove that MS Powerpoint has a relationship and affects the academic performance of students in the Senior High School of Paranaque National High School-Main. True Experimental Design were used by the researchers that selection of participants and assignment of the participants to groups in the study were randomly executed. The purpose of using true experimental research is to determine the significant difference between the Post-test score and the academic performance of two different groups that will expose to the two different teaching environment. The used of MS PowerPoint as teaching material and the used of traditional teaching materials.The general findings revealed that there is a significant difference of point -6.516, -17. 820 and -12. 831 in the pre-test and post-test scores in terms of their subject in Math, English and Science. Interpreting the mean, the study revealed that MS PowerPoint shows an improvement of the experimental group according to Analytic Skills, Evaluative Skills and Attitude are all in “agreed” with a general weighted mean of 3.96, 4.24 and 4.02, respectively. The experimental group has shown an improvement in their academic performance in terms of all three subjects.It is recommended that the principal of the school should encourage the teacher to use MS PowerPoint for their teaching, government should provide tools appropriate technology like PowerPoint to enhance quality of education and the teacher must undergo seminars and workshops for re-training to enable them to use the software properly.